Measurement of CP violation in $B_s^0 → φφ$ decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Akar, S; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (American Physical Society, 2014)
A measurement of the decay time dependent CP-violating asymmetry in $B_s^0 → φφ$ decays is presented, along with measurements of the $T$-odd triple-product asymmetries. In this decay channel, the CP-violating weak phase arises from the interference between $B_s^0$-$\bar{B}_s^0$ mixing and the loop-induced decay amplitude. Using a sample of proton-proton collision data corresponding to an integrated luminosity of $3.0\, fb^{-1}$ collected with the LHCb detector, a signal yield of approximately 4000 $B_s^0 → φφ$ decays is obtained. The CP-violating phase is measured to be ${φ_s =-0.17±0.15\mathrm{\,(stat)}±0.03\mathrm{\,(syst)}}$ rad. The triple-product asymmetries are measured to be ${A_U=-0.003±0.017\mathrm{\,(stat)}±0.006\mathrm{\,(syst)}}$ and ${A_V=-0.017±0.017\mathrm{\,(stat)}±0.006\mathrm{\,(syst)}}$. Results are consistent with the hypothesis of CP conservation.